Analysis Structure and Function Cooling System on Unit D155A-6 - Hasan Basri; Anwar Ilmar Ramadhan; Ery Diniardi (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2018)
As time went on many problems were encountered in the unit, one of which was the problem experienced by the D155A-6 unit, which was overheating troubleshooting caused by abnormal fan motors. In handling the problem, it is difficult to determine the data of the motor fan. Therefore, an initiative is needed to create tools to help deal with problems that occur. The purpose of this study is the manufacture of adapter tools for measurement of hydraulic pressure fan motors in troubleshooting the overheat engine in D155A-6 units. The results of this study are analyzing the structure and function of the cooling system in troubleshooting the overheat engine in the D155A-6 unit.